A semi-membrane ring element for the linear-elastic stress analysis of pipe elbows under in-plane bending - Melo, F. J. M. Q. de
A semi-membrane deformation ring element is presented. The displacement field involves a combination of first degree interpolation polynomials for the longitudinal direction and Fourier series in the meridional or transverse section. The possible boundary conditions for these kind of shells, namely rigid or warping endflanges and tangent terminations, are readily inserted in this ring element. Results concerning transverse section stresses and flexibility factors are calculated and discussed.